Records request response rate and vaccination status of first-time college students at a mid-sized Midwestern university. Issue 6 (24th August 2022) - Larsen, Alexandra; Cedergren, Anders
Abstract: Objective: The purpose of this study was to establish the response rate of first-time college students to a vaccination records request, and to obtain student vaccination rates for selected vaccines. Participants : Student health records for the fall 2018 cohort of first-time college students were reviewed. Methods : Vaccination and response rates were compared based on sex, race/ethnicity, and home state. Results : There was a 66% response rate to the vaccination records request with no difference in response rate based on student demographics. Students exceeded most of the Healthy Campus 2020 vaccination targets. The human papillomavirus (HPV) and meningitis ACWY vaccines had the greatest room for improvement. Female students were significantly more likely to have a completed HPV vaccine series. Conclusions : Records response rates may be improved by students accessing and reporting state vaccination information during a required orientation. Following (CDC) guidelines for vaccination success may improve vaccination rates for HPV and menACWY.